A simbólica do mal na hermenêutica fenomenológica de Paul Ricoeur - Rodrigues, Rafael Mafalda (2018)
This paper presents the symbolic of the evil developed by the hermeneutic and phenomenological method of the French author Paul Ricoeur (1913-2005). Within the delimited scope, two aspects are central: the first is the description of the hermeneutic and phenomenological method developed by Ricoeur; the second is to expose the author's interpretive work on the symbols of the religious confession of evil which he considers essential to the Western mentality, namely the symbols and myths belonging to the Hebrew, Christian, Hellenic, and ancient Middle Eastern culture. We will explore the philosophical presuppositions that lead the author towards the problematic of evil, especially the influences of the philosophy of existence mostly developed in the twentieth century, as well as Husserl's phenomenology. The concern of this stage is to show the reader the "pre-symbolic" period of Ricoeur, at the beginning of the development of his philosophy of the will. In the second stage, we intend to carry out a somewhat more detailed explanation of the methodological transition of the philosophy of Ricoeur that goes from a pure phenomenology to a phenomenological hermeneutics. Ricoeur will call his transition from "hermeneutic graft to phenomenology," and the reason for the transition of method lies precisely in the limits she had glimpsed in attempting to address the problem of evil within an eidetic description. Ricoeur intends to bring the hermeneutic problem of the semantics of the multivocal expressions into phenomenology. There is a presupposition that operates to the bottom of the hermeneutic conception of Ricoeur, that is that the access to the understanding of itself is always mediated by the signs of the culture. The purpose that animates the methodological discussion of the second chapter is to bring greater intelligibility to the interpretative effort that will be exposed in the next stage, where we will reproduce directly and integrally the exegetical work on the symbols that Ricoeur performs in Symbolic of the Evil of 1960. structural and eidetic approach that we will expose in the first stage for the typological approach of the symbols and myths that we reserve for the end of this work are contrasting, and it is at this point of divergence that we seek to elucidate the suspension of the chronological exposition of the philosophy of the will of Ricoeur, who passes from the phenomenological description of the will to the apprehension of the moment of eruption of the will that descends to evil action, and to the evil suffered.